2011
DOI: 10.1109/tasl.2010.2047755
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Perceived Material in an Impact Sound Synthesizer

Abstract: In this paper, we focused on the identification of the perceptual properties of impacted materials to provide an intuitive control of an impact sound synthesizer. To investigate such properties, impact sounds from everyday life objects, made of different materials (wood, metal and glass), were recorded and analyzed. These sounds were synthesized using an analysis-synthesis technique and tuned to the same chroma. Sound continua were created to simulate progressive transitions between materials. Sounds from thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 48 publications
2
65
0
1
Order By: Relevance
“…Concernant les sons de violon, des adjectifs reviennent souvent comme dur, lumineux, plein, chaud (harsh, bright, full, warm) [Alluri 2010] ou éffilé, sombre, clair, étroit (sharp, dark, clear, narrow ) [Stepanek 2005]. Dans un registre différent, les attributs bois, métal, verre (wood, metal, glass) ont été utilisés pour discriminer perceptivement la synthèse de sons d'impacts [Aramaki 2009, Aramaki 2011.…”
Section: Descripteurs Et Espaces De Timbreunclassified
“…Concernant les sons de violon, des adjectifs reviennent souvent comme dur, lumineux, plein, chaud (harsh, bright, full, warm) [Alluri 2010] ou éffilé, sombre, clair, étroit (sharp, dark, clear, narrow ) [Stepanek 2005]. Dans un registre différent, les attributs bois, métal, verre (wood, metal, glass) ont été utilisés pour discriminer perceptivement la synthèse de sons d'impacts [Aramaki 2009, Aramaki 2011.…”
Section: Descripteurs Et Espaces De Timbreunclassified
“…Concerning the object, it has been shown that the damping behavior of each partial characterizes the perceived material of an impacted object [14]. In line with this result, a damping law defined by a global and a relative damping behavior was proposed to control the perceived material in an impact sound synthesizer [15]. Concerning the action, recent studies focused on the synthesis of continuous interaction sounds such as rubbing, scratching and rolling [16][17][18].…”
Section: Perceptually Informed Friction Sound Synthesismentioning
confidence: 99%
“…Mapping between descriptors and signal parameters -Γ(t) represents the mapping between the descriptors and the fundamental frequency, the velocity and the pressure -f (n,0) is the n-th mode of the vibrating object (wineglass or string). Note that in each case the resonant filter bank that models the material and the shape of the object has to be calibrated accordingly [15,26] .…”
Section: Signal Modelmentioning
confidence: 99%
“…The noise wavetable represents the profile of the surface which is rubbed. Resonant filter bank simulates the resonances of the rubbed object and is characterized by a set of frequency and bandwidth values [1,2]. This synthesis model is particularly well tuned for our study, it indeed enables to generate a synthetic friction sound which varies only according to the velocity of the gesture.…”
Section: A Synthesis Model Of Friction Soundsmentioning
confidence: 99%
“…The information that enables to identify the nature of the sound source was defined as a structural invariant. For instance, it has been shown that impact sounds contain sufficient information to enable the discrimination between the materials of impacted objects [47,18,2]. The information that specifies the type of change is known as a transformational invariant.…”
Section: Introductionmentioning
confidence: 99%